Discovery of 2-thiobenzimidazoles as noncovalent inhibitors of SARS-CoV-2 main protease. (15th September 2022) - Deodato, Davide; Asad, Nadeem; Dore, Timothy M.
Graphical abstract: Abstract: The discovery of antiviral agents against SARS-CoV-2 is an important step toward ending the COVID-19 pandemic and to tackle future outbreaks. In this context, the main protease (M pro ) represents an ideal target for developing coronavirus antivirals, being conserved among different strains and essential for survival. In this work, using in silico tools, we created and validated a docking protocol able to predict binders to the catalytic site of M pro . The following structure-based virtual screening of a subset of the ZINC library (over 4.3 million unique structures), led to the identification of a hit compound having a 2-thiobenzimidazole scaffold. The inhibitory activity was confirmed using a FRET-based proteolytic assay against recombinant M pro . Structure-activity relationships were obtained with the synthesis of a small library of analogs, guided by the analysis of the docking pose. Our efforts led to the identification of a micromolar M pro inhibitor (IC50  = 14.9 µM) with an original scaffold possessing ideal drug-like properties (predicted using the QikProp function) and representing a promising lead for the development of a novel class of coronavirus antivirals.